Analisis peran senam otak terhadap fungsi kognitif lansia: A literature review - Juwari, Juwari; Ardian, Iwan; Luthfa, Iskim; Setyowati, Wahyu Endang (Holistik Jurnal Kesehatan, 2025)
Background: The elderly are an age group vulnerable to cognitive decline due to degenerative processes. Impaired cognitive function can impact quality of life, independence, and the risk of dementia. One non-pharmacological intervention considered effective in maintaining and improving cognitive function in the elderly is brain gym, which combines simple physical movements with mental stimulation. Purpose: To analyze the role of brain gym on cognitive function in the elderly. Method: Literature review research of scientific articles through research journal databases and internet searches related to the role of brain gymnastics on cognitive function in the elderly for the period 2018 to 2025. The literature review process begins with topic selection, followed by a study search through Google Scholar, PubMed, Scopus, and EBSCO sites, with the search keywords "Brain Gym", OR "Brain Gym" AND "Cognitive Function", OR "cognitive" AND "Elderly". The selection of article eligibility is carried out systematically following the PRISMA format, including the stages of identification, screening, and selection of articles for further analysis. Results: An analysis based on a review of 10 articles shows that brain gymnastics has an impact on improving cognitive function in the elderly. Brain gymnastics is effective when performed at least once a week for 15 minutes over a period of 6 weeks or more. This duration can improve blood flow and oxygen supply to organs, especially the brain, resulting in improved concentration and cognitive function. Conclusion: Increased physical activity such as aerobics, strength training, or brain gymnastics has been shown to significantly impact cognitive function. Performing gymnastics for at least 15 minutes once a week within 6 weeks can improve cognitive function in the elderly and provide health benefits, including increased alertness, concentration, and memory. Suggestion: It is hoped that brain gymnastics will become a mandatory program for the elderly in community health centers throughout Indonesia to support the quality of life of the increasing number of elderly. Furthermore, community health centers can also serve as educational centers for families and caregivers about the importance of maintaining brain health in old age.   Keywords: Brain Gymnastics; Cognitive Function; Elderly.   Pendahuluan: Lansia merupakan kelompok usia yang rentan mengalami penurunan fungsi kognitif akibat proses degeneratif. Fungsi kognitif yang terganggu dapat berdampak pada kualitas hidup, kemandirian, serta risiko terjadinya demensia. Salah satu intervensi non-farmakologis yang dinilai efektif dalam mempertahankan dan meningkatkan fungsi kognitif lansia adalah senam otak (brain gym), yang menggabungkan gerakan fisik sederhana dengan stimulasi mental Tujuan: Untuk menganalisis peran senam otak terhadap fungsi kognitif lansia. Metode: Penelitian literature review artikel ilmiah melalui database jurnal penelitian, pencarian di internet terkait dengan peran senam otak terhadap fungsi kognitif pada lansia dalam rentang waktu 2018 hingga 2025. Proses literature review dimulai dengan pemilihan topik, dilanjutkan dengan penelusuran studi melalui situs Google Scholar, PubMed, Scopus dan EBSCO, menggunakan kata kunci dalam pencarian adalah “Senam Otak”,OR ”Brain Gym” AND ”Fungsi Kognitif” OR “cognitive”AND “Lansia” OR “Elderly”. Seleksi kelayakan artikel dilakukan secara sistematis mengikuti format PRISMA, mencakup tahap identifikasi, penyaringan, dan pemilihan artikel untuk analisis lebih lanjut. Hasil: Analisis berdasar telaah pada 10 artikel menunjukkan bahwa, senam otak memiliki pengaruh terhadap peningkatan fungsi kognitif pada lansia, senam otak efektif dilakukan minimal 1 kali dalam seminggu dengan durasi 15 menit dalam jangka waktu 6 minggu atau lebih dengan durasi ini dapat melancarkan aliran dan volume pasukan darah yang membawa oksigen ke organ tubuh terutama otak, sehingga terjadi peningkatan konsentrasi dan fungsi kognitif. Simpulan: Peningkatan aktivitas fisik, seperti aerobik, latihan kekuatan, atau senam otak telah telah terbukti signifikan memiliki hubungan dengan fungsi kognitif. Senam selama minimal 15 menit dengan durasi 1 minggu sekali dalam 6 minggu dapat terjadi peningkatan fungsi kognitif pada lansia dan memperoleh manfaat kesehatan antara lain dapat meningkatkan kewaspadaan, konsentrasi, dan memori. Saran: Diharapkan agar senam otak dijadikan program wajib bagi para lansia di puskesmas di seluruh Indonesia sebagai upaya mendukung kualitas hidup lansia yang semakin meningkat jumlahnya. Selain itu, puskesmas juga dapat berperan sebagai pusat edukasi bagi keluarga dan caregiver tentang pentingnya menjaga kesehatan otak pada usia lanjut.   Kata Kunci: Fungsi Kognitif; Lansia; Senam Otak.